Impact of Critical Success Factors on ERP Implementation: Typical Organizations in Sri Lankan Context (Global Journal of Computer Science and Technology, 2019)
Enterprise Resource Planning system is a software that suitable for the user to earn more ROI by involving business activities. By the way, most organizations are still afraid to adopt this to their organizations. The reason is the high-cost wastage, and also bankruptcy. But it is not true at all the time. ERP can implement to small and medium-sized organizations too. To clarify these points, the paper focuses on the critical factors that affect the success of an ERP implementation process. It will do by a conceptual framework. It review and assertion of 15 hypotheses will carry out using "structural equation modeling technique". The definition of multi-variable technology used since the ability to check multiple linear connections at once simultaneously depends on one or more variables dependently and independently
Keywords: enterprise resource planning; critical success factors; stakeholders